Monthly and Annual Distribution of Both the Frequency of Rainy Days and Rainfall Intensity in Peninsular Malaysia - Camerlengo, Alejandro Livio; Somchit, Nhakhorn (Universiti Putra Malaysia Press, 2000)
The aim of this study is to analyze both the monthly and the annual distributions of both the frequency of rainy days and the rainfall intensity in Peninsular Malaysia. The most relevant findings of this study may be summarized as: (a) the monthly distribution of the frequency of rainy days is similar to the monthly rainfall distribution at the western side of the principal mountain range; (b) an important gradient of both the frequency of rainy days and the rainfall intensity is recorded at the Titiwangsa mountain range where a maximum is observed at its western side and a minimum at its eastern side; (c) the distribution of both the frequency of rainy days and the rainfall intensity is very homogeneous from the eastern side of the mountain range up to a distance of 50 km from the east coast; and (d) minimum of both the frequency of rainy days and intensity rainfall is recorded in the northwestern sector of the Peninsula during the boreal winter.